PRE-CENOZOIC TECTONIC DEFORMATION PHASES IN THE MUONG XEN AREA, NGHE AN PROVINCE - Minh*, Nguyen Ba; Vuong, Nguyen Van (Vietnam Journal of Earth Sciences, 2016)
The Ca River fault zone, located in the north- Central region, is one of the deformation zones having a complex structure, high level of folding and deformation, but producing very low grade metamorphism. Studies of deformation conducted in the Muong Xen area, northwest of the Ca River fault zone, show that, the Ca River fault zone had undergone at least three deformation phases before the Cenozoic. The first (oldest) deformation phase is characterized by plane, reversed and overthrust folds NW-SE direction. The second deformation phase is characterized by large Z-shaped tilted folds, deformed those structures formed in the first deformation phase. Age of these two deformation phases is marked by a pre-Late Triassic clino-unconformable plane. The third deformation phase formed structures, which altered much of the previous stage’s structures, having form and feature almost similar to those of the first folding phase. These three deforming-phase structures were subsequently effected by tectonic activities during the Cenozoic. References Bui Van Thom (1996). Findings of active characteristics of Song Ca fault zone in Cenozoic. Geological Resources, Centre of Science and Technology, Hanoi, I, 59-67. Bui Van Thom (2001). Characteristics of neotectonic activities in Da Krong - Hue fault zone. Journal of Geology, A , 267, 64-75. Bui Van Thom (2001). Determination of the nature of active fault zones in the North Central region (3 conjugate fracture systems). Journal of Earth Sciences, the Center for Science and Technology, 23 (4), 362-369. Bui Van Thom (2002). Some characteristics of neotectonic faulting in the North Central region, PhD Thesis. Institute of Geological Sciences. Bui Van Thom , 2005. Dynamic zone of neotectonic faults and related geohazards in the North Central region. Vietnam Journal of Earth Sciences, 27 (3), 223-230. Bui Van Thom , 2008. Neotectonic activity and its effects on the development of geological hazards in the North Central region. Proceedings of national scientific conference on geological hazards and prevention solutions. Construction Publishing House, p. 46-48. Cao Dinh Trieu et al., 2003. The active fault zones in the northern part of Vietnam’s territory. Journal of Geology, A , 279, 8-19. Cao Dinh Trieu et al. ,2008. Some features of seismotectonics in Southeast Asia. Journal of Geology, A, 306, 3-13. Cao Dinh Trieu, Nguyen Danh Soan, 1998. The main fault systems in Vietnam’s territory on the basis of analysis of gravity, magnetism and satellite images. Journal of Geology, A, 247, 17- 27. Cao Dinh Trieu, Pham Huy Long , 2002. Faulting tectonics in Vietnam’s territory, Science and Technics Publishing House. Claude Lepvrier, Henri Maluski, Nguyen Van Vuong, Delphine Roques, Valerica Axente, Claude Rangin , 1997. Indosinian NW-trending shear zones within the Truong Son belt (Vietnam) 40Ar/39Ar Triassic ages and Cretaceous to Cenozoic overprints. Tectonophysics, 283(1-4), 105-127. Claude Lepvrier, Henri Maluski, Vu Van Tich, A. Leyreloup, Phan Truong Thi, Nguyen Van Vuong , 2004. The Early Triassic Indosinian orogeny in Vietnam (Truong Son Belt and Kontum Massif); implications for the geodynamic evolution of Indochina. Tectonophysics, 393(1-4), 87-118. Claude Lepvrier, Nguyen Van Vuong, Henri Maluski, Phan Truong Thi, Vu Van Tíich, 2007. Indosinian tectonics in Vietnam. Comptes Rendus Geoscience, 340(2-3), 94-111. Junlai Liu, Tran My Dung, Yuan Tang, Nguyen Quang Luat, Tran Thanh Ha Jiafu Chen, Zhaochong Zhang, Zhidan Zhao , 2012. Permo-Triassic granitoids in the northern part of the Truong Son belt, NW Vietnam: Geochronology, geochemistry and tectonic implications. Gondwana Research, 22(2), 628-644. Korea Mining Promotion Corporation , 1995. Report on the joint geological and mineral survey in the Huong Khe area, Ha Tinh province, Vietnam. Geological Archives. Le Duy Bach, Ngo Gia Thang ,2003. North Central tectonic structure. Journal of Earth Sciences, 25 (1), 66-72. Ngo Gia Thang ,1999. Faulting tectonics of Tuong Duong map sheet group. Geology and Minerals of Vietnam, the 40th anniversary of the establishment of the Northern Geological Mapping Division. p. 194-212. Nguyen Ba Minh (ed.), 2005. The geological and mineral map at 1:50,000 scale of Muong Xen map sheet group. Geological Archives. Nguyen Ba Minh, Dao Nguyen Viet, 2004. Structural - tectonic features in Muong Xen zone, Nghe An. Geology and Minerals of Vietnam, the 45th anniversary of the establishment of the Northern Geological Mapping Division, p. 117-128. Nguyen Van Hoanh, 1987. Tectonic development history of North Central Vietnam and its related endogenous mineral resources. Doctor of Science Thesis on Geography - Geology, Hanoi University of Mining - Geology. Nguyen Van Vuong , 1998. Multiphase and coaxial tectonic evolution of Central Vietnam during Mesozoic and Cenozoic. Journal of Geology B (11+12), 155-163. Nguyen Van Vuong, 1998. Multiphase and coaxial tectonic evolution of the North Central Vietnam folded system in Mesozoic and Cenozoic. Abstracts of the 1st scientific conference, VNU University of Science, Geology Sector, p. 21-22. Nguyen Van Vuong, 2009. The fault zones in the North Central Vietnam. Geology and Resources of Vietnam. Publishing House for Science and Technology, 427-429. Nguyen Van Vuong, Claude Lepvrier, Phan Van Quynh, Claude Rangin, 1995. Deformation along the Ca River fault zone and Tertiary tectonics. Abstracts of Cenozoic evolution of the Indochina peninsula, 77. Phan Trong Trinh (Editor), 2005. Research on the effects of neotectonics on geohazards in the North Central region. The ministry-level scientific research project, Institute of Geological Sciences. Phan Truong Thi, 1995. Indosinia geoblock in the Indosinian tectonic movement in Indochina and East Sea in Cenozoic. Report in The third Scientific Conference on Geology. 121-136.